Factors Related To Readiness To Respond To Fire Emergencies Among Employees Of Serang District Regional Hospital In 2023 - Puji Eka Mathofani (PROFESSIONAL HEALTH JOURNAL, 2024)
The high number of fire cases that occur every year makes fire disasters a serious problem for human life. Emergency Response Preparedness is a combination of methods used in buildings to warn people of emergencies, provide a place of rescue, limit the spread of fire, extinguish fires. The aim of this research is to determine the description and relationship of fire emergency response preparedness, knowledge, attitudes, fire protection facilities and infrastructure and training. This research design uses cross-sectional. The sample was determined based on the accidental sampling method with 85 employees as respondents. The results of the analysis show that 62.4% of employees are alert in fire emergency response preparedness, 51.8% have good attitudes, 52.9% have good knowledge, 62.4% have had training, 55.3% have good fire protection facilities and infrastructure. The results showed that attitudes (P value = 0.00), knowledge (P value = 0.00), training (P value = 0.111), fire protection facilities and infrastructure (P value = 0.00). The suggestion from this research is that it is necessary to improve code blue training on fire emergency response preparedness.